2021
DOI: 10.1111/jpn.13614
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mushroom powder and vitamin D2‐enriched mushroom powder supplementation on the growth performance and health of newly weaned pigs

Abstract: A complete randomised block design experiment was conducted to examine the effects of mushroom powder (MP) and vitamin D2‐enriched mushroom powder (MPD2) on growth performance, faecal scores, coefficient of apparent total tract digestibility (CATTD) of nutrients and selected microflora in weaned pigs up to day 35 post‐weaning. One hundred and ninety‐two weaned pigs (7.8kg [SD 1.08kg]) were blocked according to live weight, sex and litter of origin and randomly assigned to the following: (T1) control diet; (T2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Maximizing the feed intake in newly weaned pigs is critical, as low feed intake immediately post-weaning negatively impacts nutrient uptake and utilization, subsequently leading to impaired gut structure and function and reduced performance [ 44 ]. The MP and MPD 2 supplementation reduced the feed intake compared with the control and ZnO, as reported by Conway et al [ 20 ]. Furthermore, MP reduced ADG compared to the ZnO group, and MPD 2 supplementation reduced ADG compared with the control and ZnO group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Maximizing the feed intake in newly weaned pigs is critical, as low feed intake immediately post-weaning negatively impacts nutrient uptake and utilization, subsequently leading to impaired gut structure and function and reduced performance [ 44 ]. The MP and MPD 2 supplementation reduced the feed intake compared with the control and ZnO, as reported by Conway et al [ 20 ]. Furthermore, MP reduced ADG compared to the ZnO group, and MPD 2 supplementation reduced ADG compared with the control and ZnO group.…”
Section: Discussionsupporting
confidence: 71%
“…Dietary supplementation with vitamin D 2 -enriched mushroom powder improved ADG and FCR in 150-day old finisher pigs [ 19 ]; however, the same effect was not observed in younger pigs [ 20 ]. Therefore, the objective of this study was to compare the molecular, physiological, and microbial effects of mushroom powder (MP), vitamin D 2 -enriched mushroom powder (MPD 2 ) and zinc oxide (ZnO) in these younger pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Conway E. et al (2021) [ 50 ] conducted a study on 192 pigs for 35 days, with an experimental protocol similar to that proposed by Dowley A. et al 2021 [ 41 ], discussed above. In terms of growth performance, pigs supplemented with MP and MPD2 had a lower ADFI at the end of the experiment ( p < 0.05) than pigs supplemented with ZnO and the control diet, with no differences in fecal counts between the experimental groups ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The results of Conway and colleagues (2021) [ 50 ] and Dowley et al (2021) [ 47 ] showed positive effects of the treatments on the amount of volatile fatty acids (VFA) produced by the gut flora, an improvement in VH (villus height) in the duodenum and jejunum in the animal models tested and an increase in the expression of SLC15A1 (solute transporter family) and FABP2 (fatty acid binding protein) in the duodenum compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[21]. As a highly nutritious functional food, various studies have confirmed that Lentinus edodes have anti-inflammatory and liver protection, anti-tumor, hypoglycemic and hypolipidemic effects, and antibacterial and other pharmacological effects [22][23][24]. At present, few studies have been related to the effects of L. edodes on the growth and health of aquatic animals, and the research on L. edodes first fermented and treated as an economic fish feed additive has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%